The Effects of Aqueous and Hydroalcoholic Extract of Eugenia Caryophyllata on Formalin Induced Pain in Male Rats - M Abbasnejad; B Keramat; S Salari; M Hosaizadeh (Institue of Medicinal Plants, ACECR, 2012)
Background : Pain is an unpleasant sensation experience that motivates when tissues are damaged or threatened. Therefore, humans have always tried to discover how to struggle against it. Nowadays people willing to use plant drugs more than chemical drugs, because chemical drugs have detrimental side effects.   Objective : In this research we studied the analgesic effects of aqueous and hydroalcoholic extract of Eugenia caryophyllata.   Methods : In this study 70 NMRI adult male rats (250 - 350 g) were randomly divided into 10 groups. In four groups of rats Aqueous extract, and in other four groups hydroalcoholic extract was injected IP at doses, 12.5, 25, 50 and 100 mg/kg. The 9th group treated with normal saline, and the last group" sham positive" received methylsalicylate (300 mg/kg). In order to evaluate analgesic effect, the formalin test was used.   Results : The results showed that the hydroalcoholic extract in comparing with normal saline decrease the pain in both parts of formalin test especially in the first 5 and 10 minutes (p<0.05). Also the results showed that the aqueous extract had analgesic effects at all doses, and the most effective doses was 100 mg/kg doses. In this research was defined the analgesic effect of methylsalicylate was better than both of extracts. Conclusion : The results suggested that at least a part of analgesic effect of Eugenia caryophyllata can be attributed to its methylsalicylate, and eugenol .